EMISSIONS FROM A 30-KW ROTATING RETORT COMBUSTOR BURNING COKING COALS - HOWARTH, CR; MALIK, AA; PEHLIVAN, D (Butterworth-Heinemann Ltd, 1993)
A 30 kW pilot-scale rotating retort combustor was designed to burn a range of coking coals and to be capable of operating with different primary and secondary air distributions. By improving the air supply arrangements it was possible to increase the peak combustion efficiency from 80 to 95%. The NO(x) emission was in the range 61-258 ppm and was subject to the well-known temperature effect. Total hydrocarbon emission levels (C1-C-7) were significantly reduced to < 230 ppm with the improved air supply arrangements. Investigations on the effect of tilt and bed depth also showed a reduction in the C1-C-7 emission to < 15 ppm at the highest bed depth. Smoke levels were below Ringelmann 2 for all operating conditions.
ENVIRONMENTAL ASPECTS OF COAL UTILIZATION AND CARBON SCIENCE CONF -- MAR 31-APR 02, 1992 -- UNIV NEWCASTLE TYNE, NEWCASTLE TYNE, ENGLAND
Keywords: EMISSIONS; RETORTING; COKING COAL